Mobile Application to Support Intelligent Supervision System for Service Buildings - Silva, Carolina Ornelas Lopes Caria da (2021)
The work developed and described in this dissertation is part of the Ambiosensing project, developed under the Portugal 2020 program. This project aims to design and develop a tool for the energy management of buildings, considering low implementation costs, adaptability, versatility, and easy maintenance in line with the premises of Industry 4.0. One of the main requirements of the project is related to the intelligent supervision of equipment, adaptability and optimization of energy efficiency and quality of comfort ofthe occupants of buildings.In this way, the problem that this dissertation addresses is related to the comfort of the occupants within a service building. For that purpose,an application for mobile devices was designed and developed complementing the Intelligent Supervision system developed in the project. This application makes it possibleto view the values of the registered environmental variables and allows the users of the spaces to leave their feedback regarding their feeling considering the presented values, in order to improve the performance of the supervision system. In addition toallowing the connection between the user and the system improving not only the system's performance, but the application also improves the user's experience inside the building.